Life-cycle assessment of biorefineries - Gnansounou, Edgard; Pandey, Ashok (Elsevier, 2017)
Life-Cycle Assessment of Biorefineries, the sixth and last book in the series on biomass-biorefineries discusses the unprecedented growth and development in the emerging concept of a global bio-based economy in which biomass-based biorefineries have attained center stage for the production of fuels and chemicals